Religiosity, idealism, and ethical consumption: the mediating effect of perceived customer effectiveness and moral obligation. Issue 1 (6th November 2020) - Alsaad, Abdallah; Saif-Alyousfi, Abdulazeez Y.H.; Elrehail, Hamzah
Abstract : Purpose: The cognitive processes through which religiosity and idealism affect ethical consumption have received little attention in prior research. This study aims to explore the influence of religiosity and idealism on ethical purchasing intention through moral obligation and perceived customer effectiveness (PCE). Design/methodology/approach: The study analyses data from 149 Muslim participants in Saudi Arabia, using structural equation modelling. Findings: The results reveal that religiosity leads to PCE but not to moral obligation and that idealism leads to both PCE and moral obligation. Mediation analysis indicated that PCE mediates the effect of both religiosity and idealism, although moral obligation only mediates the effect of idealism. Research limitations/implications: This research enriches the understanding of ethical consumption and contributes to the debate on how religiosity and idealism affect ethical consumption. It also has significant implications for theory and the development of sustainable marketing initiatives. Marketing campaigns and other promotional activities may focus on the interconnection between ethical purchase and the religious and ideology dimensions of consumers. Also, while formulating a communication strategy, it is necessary to emphasize the religious dimension of the sustainable use of the product. Originality/value: Moral obligation and PCE have been shown as cognitive and psychological mechanisms explaining the links between religiosity or idealism and ethical purchasing behaviour.